2008
DOI: 10.1073/pnas.0806159105
|View full text |Cite
|
Sign up to set email alerts
|

Delayed plasticity of inhibitory neurons in developing visual cortex

Abstract: During postnatal development, altered sensory experience triggers the rapid reorganization of neuronal responses and connections in sensory neocortex. This experience-dependent plasticity is disrupted by reductions of intracortical inhibition. Little is known about how the responses of inhibitory cells themselves change during plasticity. We investigated the time course of inhibitory cell plasticity in mouse primary visual cortex by using functional two-photon microscopy with single-cell resolution and genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
105
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(121 citation statements)
references
References 40 publications
(68 reference statements)
14
105
2
Order By: Relevance
“…Recently, it has been reported that both types of neurons showed the similar distribution of ODIs in GAD67-GFP knock-in mice at P25, P28, P30, and P35 (Gandhi et al, 2008). This seemingly different result from the present study may reflect the reduction in the GABA content in the brain of GAD67-GFP knock-in mice, although other factors such as different anesthetics are not completely excluded.…”
Section: Binocularity Of Gabaergic Neuronscontrasting
confidence: 55%
See 1 more Smart Citation
“…Recently, it has been reported that both types of neurons showed the similar distribution of ODIs in GAD67-GFP knock-in mice at P25, P28, P30, and P35 (Gandhi et al, 2008). This seemingly different result from the present study may reflect the reduction in the GABA content in the brain of GAD67-GFP knock-in mice, although other factors such as different anesthetics are not completely excluded.…”
Section: Binocularity Of Gabaergic Neuronscontrasting
confidence: 55%
“…If GABAergic neurons play such a role in visual cortical plasticity, their binocular responsiveness and modifiability of this property to monocular visual deprivation may be different from those of excitatory neurons. It is rather surprising that the questions of whether the binocular responsiveness and experience-dependent plasticity are different between the two types of neurons remain essentially unanswered, although there was a study using glutamate decarboxylase 67 (GAD67)-green fluorescent protein (GFP) knock-in mice (Gandhi et al, 2008), in which the GABA content in the brain is abnormally low because of destruction of the endogenous GAD67 gene (Tamamaki et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3A shows examples of PSP and AP responses of pyramidal neurons of the various laminae, averaged over 30 stimulus presentations. For each neuron, I computed an ocular dominance index (ODI), defined as (C Ϫ I)/(C ϩ I), where C and I are the amplitudes of visual responses to independent contralateral and ipsilateral eye stimulation, respectively (Rittenhouse et al, 1999;Pizzorusso et al, 2002;Mrsic-Flogel et al, 2007;Gandhi et al, 2008). This index varies from Ϫ1 to ϩ1 depending on whether cells are dominated by the ipsilateral or contralateral eye, respectively, whereas the ODI is 0 for perfectly binocular neurons.…”
Section: Binocularity Of Synaptic Inputs Is Not Uniform: Psp Responsementioning
confidence: 99%
“…However, even when the recording positions were reconstructed (Shatz and Stryker, 1978;Gordon and Stryker, 1996;Issa et al, 1999), the identity of recorded neurons remained uncertain. This is important because plasticity is cell-type specific even within a layer (Gandhi et al, 2008;Mainardi et al, 2009;Yazaki-Sugiyama et al, 2009). In addition, extracellular recordings are biased toward highly spiking cells, and firing rates depend on the laminar and cellular identity in rodent V1 (Niell and Stryker, 2008;Medini, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in layer 4, where ODP is initially weak or absent (11), connections between FS interneurons and pyramidal neurons can be strengthened by MD (14). Previous work attempted to track ODP in individual cortical neurons over time (15), but did not address the relative time course and nature of plastic changes in excitatory vs. inhibitory circuits during ODP (10,(16)(17)(18). The role for ongoing network activity in sleep (vs. waking experience) in these processes is also unknown.…”
mentioning
confidence: 99%